Single-Center Retrospective Analysis of Risk Factors for Hydrocephalus After Lateral Ventricular Tumor Resection - Zhang, Chengda; Ge, Lingli; Li, Zhengwei; Zhang, Tingbao; Chen, Jincao (Frontiers in Surgery, 2022)
Objective There is no general consensus on the placement of preoperative and intraoperative external ventricular drainage (EVD) in patients with lateral ventricular tumors (LVTs). The aim of this study was to identify the predictors of postoperative acute and persistent hydrocephalus need for postoperative cerebrospinal fluid (CSF) drainage and guide the management of postoperative EVD in patients with LVTs. Methods We performed a single-institution, retrospective analysis of patients who underwent resection of LVTs in our Department between January 2011 and March 2021. Patients were divided between one group that required CSF drainage and another group without the need for CSF drainage. We analyzed the two groups by univariate and multivariate analyses to identify the predictors of the requirement for postoperative CSF drainage due to symptomatic intracranial hypertension caused by hydrocephalus. Results A total of 97 patients met the inclusion criteria, of which 31 patients received preoperative or intraoperative EVD. Ten patients without prophylactic EVD received postoperative EVD for postoperative acute hydrocephalus. Eleven patients received postoperative ventriculoperitoneal(VP) shunt subsequently. Logistic regression analysis showed that tumor invasion of the anterior ventricle (OR = 7.66), transependymal edema (OR = 8.76), and a large volume of postoperative intraventricular hemorrhage (IVH) (OR = 6.51) were independent risk factors for postoperative acute hydrocephalus. Perilesional edema (OR = 33.95) was an independent risk factor for postoperative VP shunt due to persistent hydrocephalus. Conclusion Postoperative hydrocephalus is a common complication in patients with LVTs. These findings might help to determine whether to conduct earlier interventions.